Macrothemis meurgeyi Daigle, 2007, from Guadeloupe is a junior synonym of Macrothemis celeno (Selys in Sagra, 1857) (Odonata; Libellulidae) - Meurgey, François (Zootaxa, 2016)
The genus Macrothemis consists of 40 Neotropical species (Garrison et al. 2006). Recently, a new species, Macrothemis meurgeyi from Guadeloupe (French West Indies), was described based on specimens from Habitation Deravin, Basse-Terre (Daigle 2007).